Вплив фінансового важелю у впровадження схем проектного фінансування в Україні - Ізмайлова, К. В. (Ways to Improve Construction Efficiency, 2012)
The substantiation of a part of extra sources of financing investments projects by criterion of value of an indicator of the financial leverage, that is changes of profitability of own capital on net profit for each percent of change of the gross revenue is considered. The material statement is accompanied by a through example.